Pengaruh Tingkat Aktivitas Eksplorasi, Ukuran Perusahaan Dan Leverage Terhadap Konservatisme Akuntansi (Studi Kasus Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2021) - Kamelia Kuswanti; Nensi Yuniarti Zs; Furqonti Ranidiah; Budi Astuti; Yudi Partama Putra (UNIVED Press, 2023)
This study aims to examine the effect of the level of exploration activity, company size, and leverage on accounting conservatism in mining companies listed on the Indonesia Stock Exchange during the 2017-2021 period. The population in this study consisted of 71 companies. The sample technique selected based on certain criteria using purposive sampling was 16 companies.This research is a quantitative research with secondary data. The data analysis technique used multiple linear regression analysis which was processed using the SPSS (Statistical Product and Service Solution) application. Methods of data collection using data documentation.The partial results of the study show that the level of exploratory activity has no significant effect in a negative direction on accounting conservatism, this can be seen from the calculated t value of -1.301, with a significance value of 0.197 > 0.05. Firm size has a significant effect in a negative direction on accounting conservatism, this can be seen from the t-value of -4.006, with a significance value of 0.000 <0.05. Leverage has no significant effect in a negative direction on accounting conservatism, this can be seen from the t-value of -0.563, with a significance value of 0.575 <0.05. The results of the study simultaneously show that the Exploration Activity Level, Firm Size, and Leverage have a significant positive effect on accounting conservatism, this can be seen from the calculated F value of 5.465 with a significance value of 0.002 <0.05